A new type of helium purifier which uses a GM cryocooler as the cold source. (April 2019) - Hu, X; Chen, J; Xu, Z
Abstract: This new type of helium purifier developed by CSIC Pride (Nanjing) Cryogenic Technology Co. Ltd. (hereafter called Pride) uses its own 10 K GM cryocooler KDE210SA-KDC6000V (1 st stage > 60 W @ 65 K, 2 nd stage > 20 W @ 35 K) as the cold source. This new type of helium purifier can increase the purity of helium gas from 95% to over 99.999%, and its purification capacity is up to 10 Nm 3 /h. Purification time is over 12 hours and regeneration time is less than 6 hours. The purification principle of this helium purifier is cryogenic condensation and freezing, Pride has an exclusive patent for this technology (Patent number is US9752824). Compared with the traditional cryogenic absorption helium purifier, its key advantage is that to operate the purifier only needs electric power and cooling water, with no need for liquid nitrogen. Such a purifier has been used in Chinese institutes, universities and gas factories, and can be integrated with a helium liquefier to form a whole system.